Resistance training as a countermeasure in women with gestational diabetes mellitus: a review of current literature and future directions - Allman, B. R.: McDonald, S.; May, L.; Borsheim, E. (Sports Medicine, 2022)
Gestational diabetes mellitus (GDM) poses a significant health concern for both mother and offspring. Exercise has emerged as a cornerstone of glycemic management in GDM. However, most research regarding this topic examines aerobic training (AT), despite substantial evidence for the effectiveness of resistance training (RT) in improving dysregulated glucose in other groups of people with diabetes, such as in type 2 diabetes mellitus (T2DM). Thus, the purpose of this paper is to review research that examined the impact of RT on markers of glucose management in GDM, and to discuss future research directions to determine the benefits of RT in GDM. Based on the current evidence, RT is effective in reducing insulin requirement, especially in overweight women, reducing fasting glucose concentrations, and improving short-term postprandial glycemic control. However, the number of studies and findings limit conclusions about the impact of RT on risk of GDM, fasting insulin concentrations, insulin resistance, ß-cell function, and intra-exercise glucose management. Overall, current evidence is accumulating to suggest that RT is a promising non-pharmacological tool to regulate circulating glucose concentrations in women with GDM, and a potential alternative or supplement to AT.